Surface magneto plasmons and their applications in the infrared frequencies - Hu, Bin (2016)
Due to their promising properties, surface magneto plasmons have attracted great interests in the field of plasmonics recently. Apart from flexible modulation of the plasmonic properties by an external magnetic field, surface magneto plasmons also promise nonreciprocal effect and multi-bands of propagation, which can be applied into the design of integrated plasmonic devices for biosensing and telecommunication applications. In the visible frequencies, because it demands extremely strong magnetic fields for the manipulation of metallic plasmonic materials, nano-devices consisting of metals and magnetic materials based on surface magneto plasmon are difficult to be realized due to the challenges in device fabrication and high losses. In the infrared frequencies, highly-doped semiconductors can replace metals, owning to the lower incident wave frequencies and lower plasma frequencies. The required magnetic field is also low, which makes the tunable devices based on surface magneto plasmons more practically to be realized. Furthermore, a promising 2D material-graphene shows great potential in infrared magnetic plasmonics. In this paper, we review the magneto plasmonics in the infrared frequencies with a focus on device designs and applications. We investigate surface magneto plasmons propagating in different structures, including plane surface structures and slot waveguides. Based on the fundamental investigation and theoretical studies, we illustrate various magneto plasmonic micro/nano devices in the infrared, such as tunable waveguides, filters, and beam-splitters. Novel plasmonic devices such as one-way waveguides and broad-band waveguides are also introduced.